2014
DOI: 10.1111/dth.12144
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of topical versus oral ivermectin as a treatment for head lice

Abstract: Many medications are available for treatment of pediculosis capitis including ivermectin. Our aim is to compare the efficacy and safety of topical versus oral ivermectin in treatment of pediculosis capitis. Sixty-two patients with proved head lice infestation were included and divided into group I (31 patients; received single topical application of 1% ivermectin) and group II (31 patients; received single dose of oral ivermectin). Treatment was repeated after 1 week for nonresponders. At 1 week after treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Ivermectin was considered an alternative treatment in this study. Its efficacy has been supported by many studies [7,17,18,22,28]. The present study revealed that the cure rates of oral IVM were 93.4%, 95.0%, and 99.4% on days 7, 14, and 28, respectively.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Ivermectin was considered an alternative treatment in this study. Its efficacy has been supported by many studies [7,17,18,22,28]. The present study revealed that the cure rates of oral IVM were 93.4%, 95.0%, and 99.4% on days 7, 14, and 28, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…Typically, the infested person will apply approximately 30 ml of topical 25% benzyl benzoate lotion thoroughly onto a dry scalp until wet and leave the lotion on the affected area for 12 to 24 hr before rinsing off with shampoo and water; application is usually repeated on Day 7. This treatment has been reported to cause irritation and burning sensations, especially in the scratched or infected scalp [17,18]. Several oral-ivermectin treatments have been studied, particularly in hard-to-treat head-lice infestations [1723].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that these municipalities have a zero prevalence of PC infestation. Furthermore, ivermectin has shown its effectiveness in the treatment of PC after oral or local administration ( Ahmad et al, 2014 ; Chosidow et al, 2010 ; Nofal, 2010 ). Coscione et al (2018) demonstrated that ivermectin used for scabies control, had a collateral benefit on head lice infestation, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Second, ivermectin is currently the only molecule used as an oral treatment against lice. For head lice, oral route avoids suboptimal shampoo application, thus reducing the emergence and transmission of resistant lice [28,[68][69][70]. For body lice, oral dosing is of particular interest to treat people having a limited access to basic hygiene services.…”
Section: New Insights Into the Mode Of Action Of Ivermectin On Licementioning
confidence: 99%